Hubungan Pengetahuan Pencegahan Demam Berdarah Dengan Indeks Jentik - Moh Alimansur; Bagus Prabowo (coba, 2012)
Dengue Fever disease in Indonesian called Demam Berdarah Dengue (DBD), concludes a disease caused by dengue virus which is until now it still become healty problem in society. DBD is an endemic which is encloses almost 300 states in the whole world. The aim of this research is, to know the correlation knowledge of dengue fever prevention with pinch index in Bandar Lor RT:23 RW:04 Mojoroto, Kediri. The design used correlational, sampling method used is simple random sampling with sample total in 51 housemates in Bandar Lor RT:23 RW:04 Mojoroto, Kediri. The data of this research taken by using questionnaire and observation. After tabulating, the data which was analyzed by using cross test SPSS for Windows 17 with approx significant 0,824. The result of research shows good criteria 10 responders (19,6%), fair 25 responders (49%), enough 6 responders (11,8%), and bad criteria criteria (19,6%). Pinch index obtained is 64,7%. While from the result of chi-square test uses SPSS for Windows 17 obtained there is no correlation of dengue fever prevention with the pinch index with coefisien 0,132 with significant level 0,824. So, we can conclude that no significant correlation between the prevention of dengue fever with pinch index.